SAT0068 Bilirubin promotes down-regulation of runx2 and up-regulation of rankl gene expression in bone explants and in osteoblastic and osteocytic cell lines. (12th June 2018) - Ruiz-Gaspà, S.; Parés, A.; Combalia, A.; Peris, P.; Monegal, A.; Guañabens, N.
Abstract : Background: In vitro studies have shown that the retained substances of cholestasis have deleterious effects in human osteoblasts and osteocytic cells. Bilirubin (BIL) and lithocholic acid (LCA) induce alterations in the proliferation, differentiation and apoptosis of osteoblastic and osteocytic cells. However, their effects in human bone tissue and in bone cell lines have not been deeply analysed. Objectives: To investigate the effects of BIL, LCA and ursodeoxycholic acid (UDCA) in gene expression of human trabecular bone explants as well as in osteoblastic (SAOS2) and osteocytic cells (MLO-Y4/MLO-A5). Methods: Bone tissue harvested from trabecular bone fragments, SAOS2 and MLO-Y4/MLO-A5 cells were cultured and treated with BIL (50 µM), LCA (10 µM) and UDCA (10/100 µM) for 24 hour. Gene expression of osteocalcin ( BGLAP ), Cbfa1 ( RUNX2 )/Osterix ( OSX ) and RANKL ( TNFRSF11 )/osteoprotegerin ( TNFRSF11B ) were quantified by real time PCR. Results: BIL diminishes RUNX2 gene expression in bone tissue (−37%), SAOS2 (−75%), MLO-Y4 (−56%) and MLO-A5 (−77%), and increases RANKL expression in 60%, 27%, 72% and 60%, respectively (p≤0.02). In bone tissue and in osteoblastic and osteocytic cells, LCA increases gene expression of BGLAP (NS) and RANKL (p≤0.03). UDCA 100 µM increases RUNX2 and OSX expression in bone tissue (78% and 82%), MLO-Y4 (72% and 80%) and SAOS2 (75% and 70%) (p≤0.03). In addition, UDCA 100 µM significantly increases expression of BGLAP, OPG and RANKL in bone tissue and in osteocytic lines. UDCA 10/100 µM counteracts the decrease in RUNX2 induced by BIL in bone tissue, SAOS2, MLO-A5 and MLO-Y4 cells. Conclusions: The retained substances of cholestasis, particularly bilirubin, cause noxious effects on transcription factors of osteoblast differentiation and on osteoclastic activators in bone tissue and in osteoblastic and osteocytic cells. Ursodeoxycholic acid reverses the harmful effects of bilirubin. These results provide new insights into the low bone formation and at some stages, high resorption, associated with chronic cholestasis. Disclosure of Interest: None declared